Manifestações de preconceitos: a presença de haitianos em Pato Branco (PR) - Duarte, Camila Correa Baptista (2018)
Brazil’s history has been marked by migration. In the last few years, many Haitian migrants have settled in Pato Branco – a city in the south-west of Paraná, which was colonized by European peoples. Although migration is a constant movement in the country, occurrences of linguistic prejudice on migrants are quite usual and, in addition to the social prejudice, they impose difficulties on the migrants’ interaction by means of language, which is made worse in the case of Haitian people. This dissertation analyzes both occurrences of prejudice on migrants – specially on Haitian people – and the perception of it by them and their teachers. In order to do that, this study carried out an explanatory field research held at Primeira Igreja Batista de Pato Branco, where professors of Universidade Tecnológica Federal do Paraná – UTFPR teach Portuguese to migrants. The data were collected by means of scripts of observation, pre-planned questionnaires, and records on field journals. The qualitative analysis relied on a dialogic discursive approach. The results show that Haitian migrants find several difficulties by moving to Brazil; moreover, they are target of several kinds of prejudice, which are increased by the lack of knowledge on Portuguese. Therefore, migrants consider important to learn Portuguese, what is shared by their teachers in that they believe that a better understanding of language would bring migrants a lot of benefits. In short, this research shows that Portuguese teaching and use have their social motivations and do not take place randomly.